2019
DOI: 10.1158/0008-5472.can-19-0369
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase 1 Protects Ovarian Cancer Cells from Ferroptotic Cell Death

Abstract: Activation of ferroptosis, a recently described mechanism of regulated cell death, dramatically inhibits growth of ovarian cancer cells. Given the importance of lipid metabolism in ferroptosis and the key role of lipids in ovarian cancer, we examined the contribution to ferroptosis of steroyl CoA desaturase (SCD1), an enzyme that catalyzes the rate-limiting step in monounsaturated fatty acid synthesis, in ovarian cancer cells. SCD1 was highly expressed in ovarian cancer tissue, cell lines, and a genetic model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
306
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(325 citation statements)
references
References 49 publications
15
306
1
3
Order By: Relevance
“…This fact points out that SCD1 is a central element of lipid metabolism and body weight control [14]. Interestingly, its deficiency is also associated with a narrow eye fissure [22] and skin abnormalities [17]. Recently, it has been demonstrated that SCD1 protects against the palmitate-induced cytotoxic effect in mesenchymal stromal cells and osteoblasts [23].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 3 more Smart Citations
“…This fact points out that SCD1 is a central element of lipid metabolism and body weight control [14]. Interestingly, its deficiency is also associated with a narrow eye fissure [22] and skin abnormalities [17]. Recently, it has been demonstrated that SCD1 protects against the palmitate-induced cytotoxic effect in mesenchymal stromal cells and osteoblasts [23].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…Cancer stem cells (CSCs) are usually associated with chemoresistance and cancer. High levels of SCD1 have also been observed in CSCs [17,31,45,67,68]. In lung tumor spheroids, SCD1 expression was significantly upregulated [67] and SCD1 inhibition with MF-438 reverts tumoral cisplatin resistance [45,69].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 2 more Smart Citations
“…With the help of EGLNs, an enzyme that contributes to the degradation of HIF-1α, c-Myc is recruited to the LSH gene promoter, upregulating LSH expression [86,130]. Another group also reports that SCD1, an enzyme that catalyzes the rate-limiting step in monounsaturated fatty acid synthesis, inhibits ferroptosis through increasing CoQ10 (Coenzyme Q-binding protein 10), an endogenous membrane antioxidant whose depletion has been linked to ferroptosis [131].…”
Section: Lymphocyte-specific Helicase (Lsh) Acts As An Epigenetic Regmentioning
confidence: 99%